Manajemen Pembelajaran PAI Sebagai upaya Meningkatkan Kedisiplinan Sholat Berjamaah Siswa SDN 188 Simangambat TB - Kasman Kasman; Meidi Meidi; Anwar Nasution; Rostina Rangkuti; Miftahul Jannah; Vani Octaviani (CV. Alim's Publishing, 2026)
This study aims to analyze the management of Islamic Religious Education (PAI) learning as an effort to improve students’ discipline in performing congregational prayers at SDN 188 Simangambat. Learning management in PAI includes planning, implementation, and evaluation strategies carried out by teachers to instill religious values and develop students’ awareness of the importance of praying together. This research uses a qualitative approach with descriptive methods to describe the role of PAI learning management in shaping students’ prayer discipline. The results indicate that effective PAI learning management can encourage students to perform congregational prayers regularly through teacher guidance, habituation programs, and a supportive school environment. Teachers play an important role as educators and role models in building students’ responsibility and obedience in carrying out religious activities. The implementation of structured learning activities, monitoring, and evaluation contributes to improving students’ discipline and spiritual character. Therefore, proper management of PAI learning is an important factor in developing students’ religious habits and strengthening Islamic character education in elementary schools.